HYGIENIC EVALUATION OF ENVIRONMENTAL INFLUENCE ON THE HEALTH OF CHILDREN FROM RURAL REGIONS OF SOUTHERN UKRAINE - V.V. Babienko; V.L. Mykhailenko (Проблеми екології та медицини)
The article analyzes the complex hygienic assessment of harmful anthropogenic environmental factors on the health of children in rural areas of southern Ukraine and reasonable measures to prevent this impact on the health of children. It was established that the highest incidence and prevalence of disorders of respiratory, digestive, cardiovascular and urinary systems inherent in the south-western district of Odessa region with multi-ethnic composition of the population is characterized by high anthropogenic load. It has been proved that the diet of children in various districts of Odessa region is characterized by major imbalance of nutrients with predominance of food rich in carbohydrates and fats of animal origin. The program of preventive measures in areas with low environmental security should include correction of food, providing drinking water quality and regulatory measures on hygienic education of the children’s population.